Cognitive Enrichment Advantage: Applications for an Interdisciplinary Approach to Adult Learning - Jonathan E. Taylor (Adult Education Research Conference, 2010)
The author proposes that Cognitive Enrichment Advantage (CEA), an approach to mediated learning, may be a strongly beneficial approach in many adult education endeavors and can be successfully adapted to adult learning contexts. Three specific areas in which CEA may be particularly helpful are adult basic education (ABE), Emancipatory education, and workforce development/training. There is some overlap in the ways in which each of these three areas could benefit from the CEA approach but all three domains within adult education could benefit from a closer examination of the overlapping concepts and relevant applications.